Recent Advances in the Recovery Techniques of Plant-Based Proteins from Agro-Industrial By-Products - Gençdağ, Esra; Görgüç, Ahmet; Yılmaz, Fatih Mehmet (Food reviews international, 2021)
High demands for plant-based proteins have led food technologists to search for new and alternative sources. This review presents and discusses recent developments in the recovery of proteins from plant origin by-products. The innovative protein extraction techniques have advantages over conventional methods as they are cheap, eco-friendly, high efficiency as well as produce versatile final products. Different recovery techniques provide variable yields and features whereas the resulting protein isolates/hydrolysates are dependent upon the type of material and process conditions. Future studies are required to exploit potential plant-origin agro-industrial by-products, and to investigate the efficiency of recovery.